(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
This study analyzes how hot rolling changes the Fe-0.55C-3Mo-10Ni-0.5W alloy steel’s microstructure, tensile strength, wear, and corrosion behaviors. Metal powders were pressed at 750 MPa pressure, and the cold-pressed samples were sintered at 5°C/min up to 1400°C for two hours in a mixed-gas environment of 90% nitrogen and 10% hydrogen. Following that, the generated steels underwent hot rolling at 40% and 80% deformation rates. The microstructures demonstrate that MoC(N), WC(N), and MoWC(N) were created and that the steels had finer microstructures and better mechanical characteristics as the deformation rate increased. As the degree of distortion increased, the wear reduced. Furthermore, the hot rolling method improved corrosion resistance, as shown by the Tafel curve analysis. The greatest factor supporting corrosion resistance was the increase in density value throughout the rolling process.